Violence and Refugees: A Study in Eve Ensler’s Necessary Targets - Abbas, Ghadeer; Naser , Alyaa (Al-Adab Journal, 2025)
Eve Ensler’s play Necessary Targets (1996) dramatises how violence in Bosnia must be understood within the context of epistemic violence exercised by the ideological apparatuses of the western powers. The play suggests that the dominant system of knowledge represents the Bosnian refugees as primitive to silence them and to maintain the superiority of the West. Using Johan Galtung’s typology of violence, this article investigates the forms of violence endured by women refugees in Bosnia. Galtung introduces three types of violence: direct violence, structural violence, and cultural violence. The article also highlights the conception of violence as a self-perpetuating cycle in order to explore the possibility of breaking it.